Conflict‐Handling Behaviors of Korean Immigrants in the United States. (23rd September 2016) - Choi, Yeju
Abstract : Although there is a great deal of literature that has focused on conflicts faced by monocultural people, cross‐cultural conflict scholars have not yet focused on the conflicts faced by bicultural people. This topic deserves more study as cultural clashes—conflicts between foreign‐born residents and Americans—are prevalent. Considering the number of the immigrants in the United States and the speed of globalization, more conflicts could arise not only in the workplace, but also anywhere else, such as between neighbors, coworkers, colleagues, peers, and even among intercultural family members. Therefore, in order to prepare for this type of conflict, this research examined conflict‐handling behaviors of bicultural people. Among many immigrants, this study focused on Korean immigrants in the United States through the Conflict Communication Scale (CCS) and compared the results with nationality, the amount of time that the immigrants have lived in the United States, the level of acculturation, and gender.